DETERMINATION OF WAITING TIME IN PATIENTS VISITING GENERAL MALE AND FEMALE OUTDOOR CLINICS - Khalid Hussain (Army Medical College Rawalpindi, 2018)
Objective: To determine waiting time of patients visiting general male and female outdoor clinics of 01 Mountain Medical Battalion, Bagh. Study Design: Descriptive cross sectional study. Place and Duration of Study: The study was carried out at 1 Mountain Medical Battalion Bagh, from Dec 2016 to Feb 2017. Material and Methods: One hundred and ninety patients selected out of all patients visiting general male and female outdoor clinics during working days were included in this study. Lottery method was used to select ten patients daily in the study period and these were then scrutinized to include those fulfilling the inclusion criteria. Waiting time to get registered, consultation and total waiting time was noted. Data collected was entered and analyzed using Statistical Package for Social Sciences (SPSS) version 17; Independent sample t-test was used to compare means between samples with the level of statistical significance set at 5% (p<0.05). Results: Waiting time to get registered for female patients was 7.24 ± 4.42 minwhile for male patients it was 8.64 ± 5.30 min. Waiting time for consultation ranged from 15.15 ± 10.50 min for female and 16.25 ± 9.89 min for male patients. Total waiting time was 22.04 ± 11.75 min for female and 24.93 ± 12.06 min for male patients. Out of all patients, 83.33% females and 87.5% male patients were seen within 30 minutes after being registered. Conclusion: Majority of patients visiting general outdoor clinics were seen within 30 minutes of their registration which is close to the international standards. There is need to further improve waiting time of patients to increase patient satisfaction. The difference of waiting time was insignificant between male and female patients.